Measurement properties of the Spanish COPM in older adult rehabilitation inpatients - Elisabet Capdevila; Mariona Portell; Eva Penelo; María Rodríguez-Bailón (Scandinavian Journal of Occupational Therapy)
Aims To analyse the measurement properties of the Spanish version of the COPM (Canadian Occupational Performance Measure) in older adult rehabilitation inpatients.Method A sample of 172 users from 17 inpatient care facilities for older adults (47% nursing homes) participated in a quantitative prospective study. We examined validity by correlating the COPM with the Barthel Index (BI), the Lawton Instrumental Activities of Daily Living scale (IADL), the EuroQol-five domains-three level questionnaire (EQ-5D-3L), and the Client-Centred Rehabilitation Questionnaire (CCRQ) and by examining associations with demographic variables. Reliability was evaluated through test-retest and responsiveness through differences in change scores in two types of care facilities.Results Participants prioritised 637 occupational performance problems, mainly in the area of self-care (70.5%). The COPM scale scores were significantly correlated with BI, IADL, EQ-5D-3L (except the pain dimension), and CCRQ (except the family involvement and continuity dimensions). COPM scores did not show statistically significant differences concerning educational level. Regarding reliability, high test-retest correlations were obtained (>.80). Nursing home users showed less responsiveness to rehabilitation than other users (change score < 2 vs. > 2 points).Conclusion and significance The Spanish COPM provides satisfactory measurement properties as a client-centred instrument in older adult rehabilitation inpatient.